Navigating Changing Consumer Behavior And Maggi’s Marketing Strategies In The Indian Market (Journal of Namibian Studies : History Politics Culture, 2023)
In the fast-paced world of consumer goods, companies must remain agile and innovative to meet shifting consumer behaviors and preferences. This study examines the marketing strategies that have contributed to Maggi's success in the Indian market, exploring how the brand evolved from a simple 2-minute noodle product to an iconic household name. Using a combination of qualitative and quantitative research methods, we investigate the various marketing tactics employed by Maggi to maintain its market dominance while adapting to changing consumer trends.Through case studies, we analyze the challenges Maggi faced, such as the 2015 crisis involving food safety concerns, and how the brand successfully navigated these issues to regain consumer trust. Additionally, we explore how Maggi's marketing strategies leveraged cultural relevance, consumer engagement, and product innovation to solidify its place in Indian culinary culture.The findings reveal that Maggi's success is rooted in its ability to create strong emotional connections with consumers, maintain a flexible approach to marketing, and consistently innovate its product offerings. The implications of this study highlight the importance of brand resilience and adaptability, providing valuable insights for companies seeking to thrive in a dynamic consumer landscape. This research underscores the significance of understanding cultural context and consumer sentiment in formulating effective marketing strategies in the consumer goods industry.